About green scarfs and “pañuelazos”. The relation between social mobilization and social memory in the fight for women’s right (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
In this article, pañuelazos are analyzed as a type of protest that involves the use of scarfs as a symbol that gives meaning to the protest. In this work there are two objectives that are connected and mutually involved. On the one hand, it aims to understand the ways in which the movement of women and feminists makes the demand for legal abortion visible in Argentina through the green scarf. By doing that, the scarf connected them with the human rights movement, especially with Madres y Abuelas de Plaza de Mayo. On the other hand, it is proposed to investigate the ways in which the women who participated in the first pañuelazo of 2018 remember and recover the history of both movements. The article is based on a relational sociological perspective that combines aspects of collective action theories with social memory studies, while mainstreaming the gender perspective and reco- vering some feminist studies on collective action and social movements.
Keywords: social mobilization, social memory, abortion, women Ìs right